The design of the constructs of cpsD and simA genes of Streptococcus iniae - Rahmanian Kooshkaki, Mohsen; Bandehpour, Mojgan; Kazemi, Bahram (Novelty in Biomedicine, 2014)
Background & Objective: Streptococcosis is one of the bacterial infections in fish, especially rainbow trout which infects brain and nervous systems of fish and is caused by S. iniae. Estimation of the impact of disease prevalence by S. iniae in fish farming in some countries is reported about 100 million dollars per year. Some of the most effective proteins in pathogenicity of these bacteria are SimA and CpsD. In order to design new and effective vaccine, in this study cloning of two genes of Streptococcus was performed into pNZ8148 vector and expressed in Escherichia coli. Materials and Methods: simA and cpsD genes were subcloned into pNZ8148 vector. Obtained constructs were transformed to expressing E. coli BL21 strain. After induction with nisin, SDS PAGE electrophoresis and Western blotting were used to confirm the procedures. Results: Using PCR with specific and universal primers, the accuracy of cloning was confirmed. Final verification of expressed protein was carried out by SDS-PAGE and western blotting. Conclusion: With regard to the obtained results, it seems that the generated gene construct in this study can be used as a vaccine against Streptococcosis in future researches.